THE INFLUENCE OF SERVICE QUALITY AND PROMOTION ON CUSTOMER SATISFACTION AT INDOMARET KLECO - Inna Nur Rokhmah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to examine the influence of service quality and promotion on customer satisfaction at Indomaret Kleco. The method used was quantitative associative, involving 50 selected individuals as participants. Data were obtained through a questionnaire, and analysis was conducted using multiple linear regression. The research findings indicate that service quality and promotion have a significant and positive influence on customer satisfaction at Indomaret Kleco, both individually and collectively. Service quality is more influential than promotion. The coefficient of determination (R²) of 0.874 indicates that the two independent variables can explain 87.4% of the variation in customer satisfaction. This study provides recommendations for management to improve service quality and promotions to maintain and enhance customer satisfaction.